Inner jet kinematics and the viewing angle towards the γ-ray narrow-line Seyfert 1 galaxy 1H 0323+342. (November 2016) - Fuhrmann, Lars; Karamanavis, Vassilis; Komossa, Stefanie; Angelakis, Emmanouil; Krichbaum, Thomas P.; Schulz, Robert; Kreikenbohm, Annika; Kadler, Matthias; Myserlis, Ioannis; Ros, Eduardo; Nestoras, Ioannis; Zensus, J. Anton
Abstract: Near-Eddington accretion rates onto low-mass black holes are thought to be a prime driver of the multi-wavelength properties of the narrow-line Seyfert 1 (NLS1) population of active galactic nuclei (AGNs). Orientation effects have repeatedly been considered as another important factor involved, but detailed studies have been hampered by the lack of measured viewing angles towards this type of AGN. Here we present multi-epoch, 15 GHz VLBA images (MOJAVE program) of the radio-loud and Fermi /LAT-detected NLS1 galaxy 1H 0323+342. These are combined with single-dish, multi-frequency radio monitoring of the source's variability, obtained with the Effelsberg 100-m and IRAM 30-m telescopes, in the course of the F-GAMMA program. The VLBA images reveal six components with apparent speeds of ∼ 1–7 c, and one quasi-stationary feature. Combining the obtained apparent jet speed ( β app ) and variability Doppler factor ( D var ) estimates together with other methods, we constrain the viewing angle θ towards 1H 0323+342 to θ ≤ 4°–13°. Using literature values of βapp and D var, we also deduce a viewing angle of ≤ 8°–9° towards another radio- and γ-ray-loud NLS1, namely SBS 0846+513.